The use of visual supports in problem solving its effects on student achievement - Aure, Diana Sillador 1948- (1979)
This study aimed to investigate on the effects of visual supports in problem solving on students' achievement. The instruments used were the entry-knowledge test, word problems, visual supports for each word problem, and the achievement test. The research was conducted at the UP College Iloilo. It was concluded that visual supports in problem solving did not produce a significant difference in the achievement scores of the students at least during the period of the study for the second year high school students of the UP College Iloilo.
Vita.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Iloilo; Teaching -- Philippines -- Iloilo -- Aids and devices; Academic achievement -- Philippines -- Iloilo; Problem solving